2018
DOI: 10.5937/fmet1801117p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of introducing dynamic constraints for buckling to truss sizing optimization problems

Abstract: In this paper the effects of adding buckling constraints to truss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Some of the most frequently used sizing optimization problems in the literature are 10, 17, and 25-bar truss problems. These examples were previously analysed in [12], where the authors, using the same models with continuous cross-section variables, showed the influence of adding the Euler buckling constraints. The addition of the Euler buckling constraints to truss structural optimization problems ensures that the optimal truss configurations can stay in the elastic zone and maintain stability.…”
Section: Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most frequently used sizing optimization problems in the literature are 10, 17, and 25-bar truss problems. These examples were previously analysed in [12], where the authors, using the same models with continuous cross-section variables, showed the influence of adding the Euler buckling constraints. The addition of the Euler buckling constraints to truss structural optimization problems ensures that the optimal truss configurations can stay in the elastic zone and maintain stability.…”
Section: Optimizationmentioning
confidence: 99%
“…A few studies which consider dynamic buckling constraints have been published in recent years [10][11][12][13][14][15]. In [12], the authors made a comparison between using and not using buckling constraints for truss sizing problems with continuous variables. In their research, they also tested existing results from the literature which do not consider this constraint and found that all models have some bar elements which would not meet buckling criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization is the process of finding solutions from a group of alternative possible solutions. These solutions necessitate better characteristics of the construction, while at the same time decreasing invested effort and expended costs [6]. Parametric truss structural optimization is an iterative process which is used to improve desired characteristics of a truss structure.…”
Section: Structural Optimization Problemmentioning
confidence: 99%
“…Authors in [6] used continuous variables for truss sizing optimization on examples with 10, 17 and 25 bars with the added dynamic buckling constraint, showing the influence of the added constraint on optimal weight compared to work in [7], which did not consider buckling. In [8] researchers used continuous cross-sectional parameters for truss optimization of sizing, shape, topology and all their combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of trusses without buckling constraints gives low masses like in [9][10][11][12], but unstable constructions. In [13,14] the differences in optimal mass of models with and without using buckling constraints were compared. The use of buckling constraints can also be found in [15] where researchers compared both mass and overall outer area of different topological cases of a roof truss to show that the minimal mass solution does not always result in savings in all other areas.…”
Section: Introductionmentioning
confidence: 99%